Ответы и объяснения

2013-04-24T15:53:13+04:00

3y-11=1-2y               2(x=2)=-3(x-1)                 2x-3(4-x)=5-(x-1)          5x-6(2x+7)=13-(x+1)

3y+2y=1+11              2x+3x=3-4                       2x-12+3x=5-x+1             5x-12x+42=13-x-1

5y=12                            5x= -1                             2x+3x+x=5+1+12             5x-12x+x=13-1-42

y=12/5                             x=-1/5                               6x=18                            -6x= -30

                                                                                      x=3                                x=5